Hillslope Processes Affect Vessel Lumen Area and Tree Dimensions - Kašpar, Jakub; Šamonil, Pavel; Krůček, Martin; Vašíčková, Ivana; Daněk, Pavel (Frontiers in Plant Science, 2021)
The height growth of trees depends on sufficient mechanical support given by the stem and an effective hydraulic system. On unstable slopes, tree growth is affected by soil pressure from above and potential soil erosion from below the tree’s position. The necessary stabilization is then provided by the production of mechanically stronger wood of reduced hydraulic conductivity. Unfortunately, the interaction between tree growth (both radial and axial) and stabilization in the soil is still insufficiently understood. Therefore, in this study we aimed to quantify the impact of hillslope dynamics on the degree of tree growth and hydraulic limitation, and the potential effect on tree height growth and growth plasticity. To evaluate this effect, we took four cores from 80 individuals of Quercus robur and Fraxinus excelsior and measured tree-ring widths and vessel lumen areas. Tree heights were evaluated using a terrestrial laser scanner, and local soil depth was measured by a soil auger. Our data showed a significant limitation of the tree hydraulic system related with the formation of eccentric tree-rings. The stem eccentricity decreased with increasing stem diameter, but at the same time, the negative effect of stem eccentricity on conduit size increased with increasing stem diameter. Even though this anatomical adaptation associated with the effect of stem eccentricity differed between tree species (mainly in the different degree of limitations in conduit size), trees showed an increase in the proportion of hydraulically inactive wood elements and a lowered effectiveness of their hydraulic system. We also observed a larger negative effect of stem eccentricity on vessel lumen area in Quercus. We conclude that the stabilization of a tree in unstable soil is accompanied by an inability to create sufficiently effective hydraulic system, resulting in severe height-growth limitation. This affects the accumulation of aboveground biomass and carbon sequestration.